Analisis Kandungan Nutrisi dan Uji Kualitas Mikrobiologi pada Susu Kedelai di Pasar Pa’ Baeng-Baeng Kota Makassar - Anastasia Susanti Jimin; Hasria Alang; Rezeki Amaliah (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Soy milk is a processed soybean seed which is rich in nutrients, making it susceptible to pathogen contamination. The aim of the study was to analyze the feasibility of consuming soy milk at the Pa'Baeng-Baeng Market, Makassar City based on its nutrient content and microbial contaminants. The method used in this study was quantitatively to see nutrient levels and MPN values, and qualitatively to see the color changes formed as an indicator of the presence of the test pathogen. Samples were obtained from two places in the Pa'Baeng-Baeng Market, namely closed and clean locations (A), and open and dirty locations and close to landfills (B). The results showed that sample A had a water content of 92.87%; ash content 0.78%; crude protein 2.31%; crude fiber 0.0030%; carbohydrates 3.61%; and 0.43% fat. Meanwhile, sample B has a water content of 92.85%; ash content 0.78%; crude protein 3.06%; crude fiber 0.0042%; carbohydrates 3.06%; and 0.24% fat. The MPN values for samples A and B were >23/mL exceeding the required SNI because they contained Escherichia coli, so they were not in accordance with SNI, but there was no Staphylococcus aureus.